General rules in consideration of international instruments which are treaty - siwutthiyaprapha, phetnaphat (King Prajadhipok’s Institute Journal, 2020)
International instruments, made by the states or international organizations, include the ones that give a rise to a legal obligation, called treaties, and the ones that do not entail legal obligation. There are not exact criteria for the consideration of whether a particular instrument evokes legal bond, so there is often a dispute between the contracting parties in interpreting the status of the instrument in question. However, the consideration of the international instruments in a form of treaty can be determined by the meaning and composition of the treaty according to international laws and the guidelines of International Court of Justice(ICJ), which are considered the general rules used as a guide to consider whether the international instrument status is treaty or not.